Casa líquida: a criação de valor e de outras economias no exercício da desobediência - Feldens, Juliana Garcia (2021)
This dissertation analyzes “Casa Líquida” and what has resulted from this performance that I have been developing since 2015 whose action is to open the house where I live with my children for other uses and other people. The experience that originated from this practice and that involved hundreds of artists started to be analyzed from an economic logic, having the notion of “value” as a fundamental element for this reflection. To do so, we present questions born from an arachnian movement (in web), and we build a theoretical foundation with authors from different areas of knowledge, such as philosophy, economics, education, art and communication with focus on studies of the body. The fact that there are no monetary values exchanged inside the house complexifies the discussion about which values make this houseperformance possible and how “more-value” is produced from the circulations it creates and what kind of economy it generates. In addition to these questions, the results of this research refer to making think and act around related themes such as alterity, the body, the notions of system, entropy, creation and politics for life